Young migrant students’ motivators and drive for obtaining education - Lindvig, Inger Kjersti; Svenni, Trine (Nordic Journal of Comparative and International Education (NJCIE), 2021)
This article investigates how students from migrant backgrounds describe their motivators and drive for obtaining an education. It is based on a qualitative study of 17 young people aged 16-24. All are students in combination classes at a large upper-secondary school in Eastern Norway and are recent arrivals in Norway with little prior education. Half aspire to higher education, while the others are applying for vocational training. In this article, we link these educational ambitions to four forms of motivation. The immigrant motivator relates to high academic expectations among parents and other family members. In addition to the immigrant motivator, there is what we refer to as the middle-class motivator, where parents of low socio-economic status exert influence in a way that can be understood as a kind of middle-class behaviour. The world-citizen motivator encompasses the students’ desires to contribute by giving something back to their home countries, the host country, and the global community. The opportunity motivator is linked to the efforts of the school community to provide an inclusive and facilitative environment for this group of students. Schools that offer adapted and differentiated teaching, customized to the needs of individual students, as with combination classes, seem to function as important protective factors.